2023
DOI: 10.1038/s41586-023-05752-y
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the germline mutation rate across vertebrates

Abstract: The germline mutation rate determines the pace of genome evolution and is an evolving parameter itself1. However, little is known about what determines its evolution, as most studies of mutation rates have focused on single species with different methodologies2. Here we quantify germline mutation rates across vertebrates by sequencing and comparing the high-coverage genomes of 151 parent–offspring trios from 68 species of mammals, fishes, birds and reptiles. We show that the per-generation mutation rate varies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
162
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(184 citation statements)
references
References 102 publications
17
162
3
2
Order By: Relevance
“…It has been hypothesised that the germline mutation rate in multicellular eukaryotes may be explained by an equilibrium between natural selection to minimise it and the power of genetic drift to overcome the effect of selection (Lynch et al 2016). However, to date, there are relatively few estimates of germline mutation rate from multicellular eukaryotes, and those estimates that we do have are patchily distributed across the tree of life (reviewed by Yoder and Tiley 2021; but see Bergeron et al 2023;Wang and Obbard 2023). On the one hand, mutation rates appear to differ markedly between some distantly related species.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesised that the germline mutation rate in multicellular eukaryotes may be explained by an equilibrium between natural selection to minimise it and the power of genetic drift to overcome the effect of selection (Lynch et al 2016). However, to date, there are relatively few estimates of germline mutation rate from multicellular eukaryotes, and those estimates that we do have are patchily distributed across the tree of life (reviewed by Yoder and Tiley 2021; but see Bergeron et al 2023;Wang and Obbard 2023). On the one hand, mutation rates appear to differ markedly between some distantly related species.…”
Section: Introductionmentioning
confidence: 99%
“…P. Martin & Palumbit, 1993). However, poikilothermy does not itself explain DNM rate variation across vertebrates (Bergeron et al, 2023), suggesting that the role of homeostasis in DNM rate is small. Our large pedigrees, each comprised of 10 offspring, make it possible to assess DNM sharing among siblings, and thus assess the degree of mosaicism in the germline genome (Goldmann et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Recent sequencing-based approaches to study germline mutation have used pedigrees to characterize germline DNM, and revealed the influence of many factors, including generation time (Bergeron et al, 2023;Carlson et al, 2018;Francioli et al, 2015;Kong et al, 2012;Wang et al, 2022), life history (Bergeron et al, 2023), and number of cell divisions (Ellegren, 2007).…”
mentioning
confidence: 99%
“…Second, sperm are potentially more affected by advancing organismal age than eggs (Bronikowski et al, 2022;Nussey et al, 2009). This pattern is due to sperm being more active and shorter lived than eggs, and male germlines having higher rates of cell divisions and mutations (Bergeron et al 2023;Crow, 2000;Fischer and Riddle, 2018;Monaghan and Metcalfe, 2019), but poorer DNA repair machinery, than female germ cells (Reinhardt and Turnell, 2019). Consequently, there may be greater transmission of accumulated mutations to offspring, via the paternal germline (Bergeron et al 2023;Campbell and Eichler, 2013;de Manuel et al, 2022;Sharma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern is due to sperm being more active and shorter lived than eggs, and male germlines having higher rates of cell divisions and mutations (Bergeron et al 2023;Crow, 2000;Fischer and Riddle, 2018;Monaghan and Metcalfe, 2019), but poorer DNA repair machinery, than female germ cells (Reinhardt and Turnell, 2019). Consequently, there may be greater transmission of accumulated mutations to offspring, via the paternal germline (Bergeron et al 2023;Campbell and Eichler, 2013;de Manuel et al, 2022;Sharma et al, 2015). Third, male reproductive senescence can affect male and female fitness due to declines in fertilisation ability of males (Johnson and Gemmell, 2012;Paul and Robaire, 2013), or due to declines in offspring quality via paternal age effects (Eisenberg and Kuzawa, 2018;Pizzari et al, 2008;Schroeder et al, 2015;Priest et al, 2002;Preston et al, 2015).…”
Section: Introductionmentioning
confidence: 99%